Research of influence the mollusks' hydrolyzate on the clinical condition of children - Крамаренко, Дмитро Павлович; Кірєєва, Олена Іванівна; Галяпа, Ірина Михайлівна (Technology audit and production reserves, 2014)
This article discusses the use of a dietary supplement "Rapamid" in the diet of children - residents of radioactive contaminated territories. The authors conducted a clinical study of the supplement. The main purpose of research is to assess the therapeutic and radioprotective properties of the hydrolyzate of molluscs "Rapamid" among children who are contaminated by radiation. It was established that a supplemental assignment of dietary supplement "Rapamid" to the normal diet and to the basic therapy contributed to more pronounced effect for children with pathologies of the digestive system compared to a control group. The authors defined a positive influence of the additive "Rapamid" on processes of cavitary digestion , as demonstrated by a decrease in symptoms of diseases such as kreatoreya, amylorrhea, steatorrhea and dysbiotic manifestations. Noted that consuming of dietary supplements "Rapamid" contributed to increasing hemoglobin and red blood cells. Radioprotective properties of dietary supplement "Rapamid" were identified in conducting research. It was confirmed by a decrease in the intensity of free radical processes in biological media of the body and more significant decrease in the content incorparative of cesium-137 compared to a control group. Was also investigated the dynamics of hematological indices of children in the application of this additive. The authors focus attention on good portability and absence of side effects of dietary supplement "Rapamid."